PKM PENGEMBANGAN OBJEK WISATA PULAU BATU LANGKAI KAMPAR-RIAU - Raja Widya Novchi; Khusnul Hanafi; Jayus Jayus; Finanta Okmayura; Raja Arlizon; Hichmaed Tachta Hinggo S (Jurnal Abdimas Bina Bangsa, 2023)
The attractiveness of a tourist object is one of the important assets that must be owned in order to improve and develop a tourist attraction because the potential attractiveness of a tourist object is what attracts tourists to that destination. In order to make a tourist attraction acceptable to tourists, a mature concept is needed so that it can have a positive effect on the development of the tourist attraction, as well as for the surrounding environment. In Limau Manis Village there is a Batu Langkai Island Tourism Object. Previously, the existence of this tourist attraction had been managed by the community but stopped due to lack of funds, land issues, lack of knowledge about tourism promotion strategies, lack of information related to tourist objects, at several points there was still quite a lot of trash scattered in the river area and there was no place to capture the moment (photo spots). The service team collaborated with residents to make organic and inorganic trash cans, make photo spots, promotion strategy workshops and provide neon boxes for Batu Langkai Island Tourism Objects